A thermo-mechanical coupling model for simulating the re-entry failure evolution mechanism of spacecraft propulsion module. (March 2023) - Liu, Zhihui; Li, Zhihui; Ma, Qiang
Abstract: A three-dimensional dynamic thermo-mechanical coupling model (TMCM) has been developed to analyze re-entry evolution mechanism of spacecraft propulsion module subjected to aerodynamic/thermal loads. Firstly, a general dynamic thermo-mechanical coupling finite element algorithm is proposed based on TMCM. The accuracy of TMCM is verified by comparison with analytical solutions of one-dimensional problem and numerical solutions of three-dimensional problem. Then, the TMCM for a complex propulsion module is established, in which all the fuel tanks, gas cylinders, support frame and cone platform are taken into account. The external heat flux and pressure of the whole propulsion module are calculated by gas-kinetic unified algorithm (GKUA). Finally, the dynamic thermo-mechanical evolution mechanism of each component structure and the influence of radiation heat transfer are discussed separately during re-entry 90 km-75 km altitude range, and materials considered are stainless steel, carbon fiber composite and aluminum alloy. Simulation results reveal the evolution process of the temperature field, displacement field and stress field of the whole propulsion module. The TMCM provides a powerful tool for accurate prediction of disintegration failure during spacecraft re-entry through thermal and structural analysis of the structure. Highlights: A general dynamic thermo-mechanical finite element algorithm with radiation effects is presented. A new one-way coupling method for calculating the thermo-mechanical response of aerodynamic and solid structures is established. The evolutionary failure mechanism at different altitudes during the re-entry process of the spacecraft propulsion module can be accurately predicted. The proposed algorithm can be widely used in numerical calculation of structures with different geometrical structures and different materials.